'They come with their own ideas of what they want': Healthcare educator, advanced practice student and manager perspectives on learning outcomes. Issue 4 (18th May 2020) - Kubiak, Chris; Walker, Susan; Draper, Jan; Clark, Elisabeth; Acton, Faye; Rogers, Jill; Rogers, Melanie; Dearnley, Christine
ABSTRACT: In post-registration, professional healthcare education, learning outcomes should reflect the needs of several stakeholders, including the professionals studying the programme, workplace managers aiming to develop their workforce, and the educators teaching the programme. This study aimed to gain a multifaceted view of how these different stakeholder groups understand the learning outcomes associated with four English, postgraduate healthcare modules designed to develop advanced healthcare practice. A concurrent mixed methodology research design was used. Online questionnaires were used to collect data from purposive samples of students and workplace managers, and semi-structured interviews were used with educators teaching on the four advanced practice modules in two English universities. The findings indicated that learning outcomes crystallise a variety of academic, regulatory and professional imperatives into a set of curriculum objectives. However, these learning outcomes-as-intended appear distinct from learning outcomes-as-enacted and as experienced. Furthermore educators, students and workplace managers have distinct perspectives on the module learning outcomes. Students and workplace managers prioritised clinical and work-specific skills, while the educators also focused on a broader range of underpinning academic outcomes. The challenges associated with shared understanding are discussed, including the inherent tension of meeting the demands and expectations of both higher education and clinical practice.